Listeriosis downregulates hepatic cytochrome P450 enzymes in sublethal murine infection. Issue 9 (27th June 2016) - Kummer, Anne; Nishanth, Gopala; Koschel, Josephin; Klawonn, Frank; Schlüter, Dirk; Jänsch, Lothar
Abstract : Purpose: Listeria monocytogenes (Lm) can cross the intestinal barrier in humans and then disseminates into different organs. Invasion of the liver occurs even in sublethal infections, however, knowledge of affected physiological processes is scarce. This study employed a sublethal murine infection model to investigate liver responses systematically by proteomics. Experimental design: Liver samples from three stages of the sublethal infection covering the initial invasion, the peak of infection, and the clearance phase (1, 3, 9 days postinoculation) were analyzed in comparison to samples from noninfected mice. Apart from flow cytometry and RT‐PCRs for immune status control, liver responses were analyzed by quantitative peptide sequencing (HPLC‐Orbitrap Fusion) using 4‐plex iTRAQ‐labeling. Results: Accurate MS characterized about 3600 proteins and statistics revealed 15% of the hepatic proteome as regulated. Immunological data as well as protein regulation dynamics strongly indicate stage‐specific hepatic responses in sublethal infections. Most notably, this study detected a comprehensive deregulation of drug metabolizing enzymes at all stages, including 25 components of the cytochrome P450 system. Conclusions and clinical relevance: Sublethal Lm infection deregulates hepatic drug metabolizing pathways. This finding indicates the need to monitor drug administration along Lm infections, especially in all patients needing constant medication.